Rural healthcare of Russia. Status, problems, prospects - V. M. Chernyshev; M. I. Voevoda; O. V. Strelchenko; I. F. Mingazov (Сибирский научный медицинский журнал, 2022)
The transformations of domestic healthcare carried out in the last three decades have not led to the planned results, and in some areas the consequences have turned out to be negative. Rural healthcare suffered the most significantly. The aim of the study was based on the analysis of the situation in the rural health care of the country to propose measures to improve it. Material and methods. The statistical data of the Ministry of Health of Russia, Rosstat, Central Research Institute of Organization and Informatization of Healthcare, as well as data on the Siberian Federal District for the period from 1990 to 2020 were used. Scientific publications on the problem under consideration have been studied. Results and their discussion. The course taken in the early 90s of the last century towards the commercialization of medicine remains. So for the period from 2005 to 2018 in the structure of the country’s medical personnel, the number of people employed in the public sector decreased from 93.6 to 86.8 % (by 237 000), whereas in private medical organizations it increased by 2.3 times. In 2020, 38.4 % of medical organizations were already private. The most significant changes have occurred in rural healthcare. The number of paramedic and obstetric stations decreased by 21.1 %, the provision of beds in hospitals is 2 times lower than the national average, and doctors are 3 times fewer than in cities. In the age structure, the share of doctors over the age of 60 increased from 13.5 % (2017) to 18.1 % (2020). The implementation of the programs “Zemsky Doctor” and “Zemsky paramedic” did not lead to an increase in the provision of medical workers in rural areas. Today, medical care is geographically available only to 49 % of villagers, for 40 % it is difficult to access, and 9 % is practically inaccessible (2 % of respondents could not answer the question). This has led to the fact that the average life expectancy of the villagers is 1.5 years lower than that of the townspeople, and the total mortality is 1.2 % higher than the national average. Conclusion. The problem of accessibility of medical care to the rural population has worsened in the last three decades. The implemented programs aimed at improving its accessibility and quality, including for rural residents, have not led to a significant positive result.